Implementing Collaborative Document Management System In Higher Education Environment - Wicaksono, Soetam Rizky (LPPM STIKI Malang, 2015)
The need of integrated data gathering in an institution often become a forgotten problem. However, this requirement should be implemented carefully depending on the institution need. For that reason, there should be a specific information system that will hold whole data in the institution as an integrated data from every department and it also must handle all synchronization process. The most appropriate and fastest solution for this problem is creating a collaborative document management system. First step in this research is analyzing the system requirements and also identifying available resources. And in its implementation, even though technically succeeded, however, it also meets constraint from user’s behavior. As this collaborative document management system already being implemented as web based application, it still need some future development in order to make the system more useful for the institution.